EVALUASI FORMULASI TABIR SURYA ALAMI SEDIAAN GEL LIDAH BUAYA (Aloe vera) DAN RUMPUT LAUT MERAH (Eucheuma cottonii) - Srie Rezeki Nur Endah; Eddy Suhardiana (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Humidity in Indonesia can reach 80% with relatively high temperatures reaching 35Â°C with intense and increasing sunlight. The use of sunscreen is necessary to protect skin health from ultraviolet radiation. Aloe vera is a plant that has strong antioxidant activity, so it can be used on the face as a moisturizer. E. cottonii red seaweed according to Zhaohui and Gao (2005) contains a composition of phycocyanin which is mycosporine acid (MAAs) and consists of imine derivatives containing chromophore aminocycloheximine UV absorbing. The purpose of this study was to obtain the results of a moisturizing gel and natural sunscreen formulation combination of Aloe vera with red seaweed. Formulation using Aloe vera with red seaweed ethanol extract varied into 3 different concentrations. Aloe vera gel was prepared from meat and seaweed extract was made by maceration with 70% ethanol. The results of the gel preparation formulation were evaluated by conducting organoleptics tests, homogeneity tests, pH tests, scatterability tests and viscosity tests. The evaluation results obtained formula I that best meets the most stable requirements.